Stability of discontinuous dynamic systems - Li, Zhengguo. (2008)
Discontinuous dynamic systems (DDS) are systems with jump phenomena and discon-tinuous motion, such as hybrid dynamic systems, fuzzy systems, jump linear systems and impulsive differential systems, etc. This research work considers the stability of DDS and it focuses on the stability of hybrid dynamic systems Some sufficient condi-tions for the stability of the various types of DDS are derived.